An Effective Oral Nanodelivery Material for Curcumin: Ingenious Utilization of Gastrointestinal Absorption Characteristics - Qiuxu An; Yuanyuan Liu; Guodong Liang; Yuewu Wang; Fengying Liang; Yunyang Bai; Chaolu Eerdun; Riqing Cheng; Haifeng Zhang; Xiaojie Lv (Molecules)
Curcumin exhibits compromised bioavailability upon oral administration due to its inherent limitations, including low aqueous solubility, poor membrane permeability, and chemical instability. Inspired by the efficient mechanism by which viruses penetrate mucus and cells, we constructed an electrically neutral and hydrophilic nanocarrier (C60-CPP5/Pser@CUR) using fullerene C60 as the matrix modified with cell-penetrating peptides and phosphoserine. CPP5 facilitates efficient cellular internalization of therapeutic agents, while the incorporation of phosphoserine serves as a charge reversal strategy. This design enables dynamic surface charge modulation to enhance curcumin’s trans-barrier delivery efficiency. Systematic in vitro and in vivo evaluations demonstrated that the synthesized carrier significantly improved the synergistic effects of mucus penetration and cellular uptake. The Caco-2 cellular uptake of curcumin-loaded carriers was 2.26 times higher than that of free drugs. In a single-pass intestinal perfusion study in rat models, this nanocarrier significantly enhanced the absorption of curcumin in the duodenal and colonic regions. In the in vivo experiments, compared with free curcumin, its Cmax and AUC0–t achieved improvements of 2.60 times and 14.70 times, respectively. This virus-mimetic platform dynamically adapts to micro-environmental demands through charge reversal mechanisms, effectively overcoming sequential biological barriers and providing a robust strategy for oral delivery of hydrophobic therapeutics.